Динамика почвенного плодородия в коллекционных насаждениях Донецкого ботанического сада НАН Украины - Поляков, А.К.; Торохова, О.Н. (Промышленная ботаника, 2006)
Dynamics studying of agrochemical soil abilities under arboreal stands of the Donetsk Botanical Gardens of the National Academy of Sciences of Ukraine showed, that during ten-year period humus level increasing took place (within the bounds 0,1-0,3%). Exchange soil acidity changed from slightly asid values (pH 6,6-6,8) to mildly alkaline ones (pH 7,5-8,2). During the period soil degradation under man-made stands was not observed. Quercus rubra Du Rei and Tilia platyphyllos Scop. were revealed as stands of maximum positive effect on soils. Tendency to organic matter content increasing on the total studying profile was observed under all stands.